INQUERITO SOROLÓGICO E MOLECULAR DO VÍRUS DA HEPATITE B EM UMA COMUNIDADE SEMI-ISOLADA DA AMAZÔNIA ORIENTAL - Gomes, M.M.S.; Bertolini, D.A.; Moreira, R.C.; Bensabath, G.; Soares, M.C.P.; Pinho, J.R.R. (Revista do Instituto Adolfo Lutz, 2002)
Ver PDF.